(untitled) (American Journal of Management, 2022)
Status hierarchies influence all human interactions, including strategic consensus in top management teams. In this conceptual paper, we articulate why strategic consensus in top management teams is likely to be more a reflection of compliance of low-status top managers with high-status top managers’ judgments than a genuine team’s agreement on the firm’s strategic priorities. We theorize how a firm’s performance can restrain and drive change in status hierarchies, thus impacting the persistence and dissolution of strategic consensus. We also articulate how a culture of dissent can minimize the impact of status hierarchies on strategic consensus. Our model has some implications for examining diversity in top management teams. Scholars have long emphasized the importance of diversity in top management teams, arguing that managers with different backgrounds and viewpoints make firms better equipped to face competitive challenges. However, status hierarchies remind us that if top managers’ ideas and contributions are weighed by their status, organizations might not easily realize the potential benefits of having a diverse top management team.